Scoto-seesaw model implied by flavor-dependent Abelian gauge charge - Duong Van Loi; N. T. Duy; Cao H. Nam; Phung Van Dong (European Physical Journal C: Particles and Fields)
Abstract Assuming fundamental fermions possess a new Abelian gauge charge that depends on flavors of both quark and lepton, we obtain a simple extension of the Standard Model, which reveals some new physics insights. The new gauge charge anomaly cancellation not only explains the existence of just three fermion generations as observed but also requires the presence of a unique right-handed neutrino $$ν _R$$ ν R with a non-zero new gauge charge. Further, the new gauge charge breaking supplies a residual matter parity, under which the fundamental fermions and $$ν _R$$ ν R are even, whereas a right-handed neutrino $$N_R$$ N R without the new charge is odd. Consequently, light neutrino masses in our model are generated from the tree-level type-I seesaw mechanism induced by $$ν _R$$ ν R and from the one-loop scotogenic contribution accommodated by potential dark matter candidates, $$N_R$$ N R and dark scalars, odd under the matter parity. We examine new physics phenomena related to the additional gauge boson, which could be observed at colliders. We analyze the constraints imposed on our model by current experimental limits on neutrino masses, neutral meson oscillations, B-meson decays, and charged lepton flavor violating processes. We also investigate the potential dark matter candidates by considering relic density and direct detection.